2015
DOI: 10.1590/0103-6351/3551
|View full text |Cite
|
Sign up to set email alerts
|

Neoliberalism, trade imbalances, and economic policy in the Eurozone crisis

Abstract: This paper analyzes the causes of the Eurozone crisis. In doing so,it carefully surveysauthors from different economic schools of thought. The paper discusses competing explanations for European current account imbalances. Remarkably, opposing views on the relative importance of cost developments and demand developments in explaining current account imbalances can be found in both heterodox and orthodox economics. Regarding the assessment of fiscal and monetary policy there is a clearer polarisation, with hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Following this reasoning, the dominant narrative is the one that most influences policymakers and socio-political decisions. As a consequence, it is not surprising that the Economic and Monetary Union (EMU) integration process was characterized by a neoliberal design and influenced by ordoliberal ideas (Dullien/Guérot 2012;Ito 2011;Stockhammer et al 2015). Kapeller et al (2017) found empirical evidence about the connection between mainstream economic models, policy-making, and political narrative within the EMU.…”
Section: Economic Theory and Narrativesmentioning
confidence: 99%
See 2 more Smart Citations
“…Following this reasoning, the dominant narrative is the one that most influences policymakers and socio-political decisions. As a consequence, it is not surprising that the Economic and Monetary Union (EMU) integration process was characterized by a neoliberal design and influenced by ordoliberal ideas (Dullien/Guérot 2012;Ito 2011;Stockhammer et al 2015). Kapeller et al (2017) found empirical evidence about the connection between mainstream economic models, policy-making, and political narrative within the EMU.…”
Section: Economic Theory and Narrativesmentioning
confidence: 99%
“…As a matter of fact, however, there is no convergence towards a consensus narrative (Stockhammer et al 2015), and national public opinions struggle to share a common European interpretation of the crisis. Müller et al (2018) analyse the European fragmented public sphere by examining key crisis-related topics in articles from four opinion-forming newspapers in Germany, France, Italy and Spain (respectively, Süddeutsche Zeitung, Le Monde, La Stampa and El País).…”
Section: Economic Narratives and The European Sovereign-debt Crisismentioning
confidence: 99%
See 1 more Smart Citation